Study of Microgastrinae Nees 1814 (Hymenoptera: Braconidae) in Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Three genera of Microgastrinae (Hymenoptera: Braconidae) have been described and illustrated from Bangladesh and a key for the genera was prepared. The genera are Apanteles Foerster, Microplitis Foerster, and Protomicroplitis Ashmead. The genus Protomicroplitis is the new record to the fauna of Bangladesh. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17240 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):147-158, 2011